Case report: Peptide receptor radioligand therapy in metastatic pediatric neuroendocrine tumors - Hlongwa, Khanyisile; Kolade, Olumayowa; Alnabulsi, Abdulilah; Steyn, Rachelle; Brink, Anita; Prasad, Vikas; More, Stuart (Frontiers in Nuclear Medicine, 2023)
Neuroendocrine tumors (NETs) are not commonly diagnosed in children. Metastatic NETs tend to have poor outcomes, and this is seen in adult and pediatric populations. The role of somatostatin receptor imaging using [68Ga]Ga-DOTA-TATE for imaging and peptide receptor radionuclide therapy (PRRT) with [177Lu]Lu-DOTA-TATE in children is currently not well established. The guidelines for treating pediatric neuroendocrine tumors are still lacking. Extensive trials have been conducted in adult patients and have demonstrated improved survival in metastatic NETs with PRRT using [177Lu]Lu-DOTA-TATE. We present two pediatric patients with metastatic NETs who were imaged with [68Ga]Ga-DOTA-TATE PET/CT and treated with [177Lu]Lu-DOTA-TATE therapy.